Tinjauan Kriminologis Terhadap Kasus Pencurian Yang Dilakukan Oleh Residivis Di Kota Kupang - Aurelio Junior Wolo Aurelio; Rudepel Petrus Leo; Rosalind Angel Fanggi (CV. Ulil Albab Corp, 2026)
This study is motivated by the increasing number of theft cases committed by recidivists in Kupang City, indicating that law enforcement and correctional efforts have not been fully effective in preventing the recurrence of criminal acts. Recidivism in theft cases is an important issue as it is related to both individual and social environmental factors influencing the offenders’ behavior. Therefore, this study aims to identify the factors causing theft by recidivists and to analyze the effectiveness of the law and sanctions applied in preventing such crimes in Kupang City. This research employs an empirical legal research method with a qualitative approach. Data were collected through direct interviews with recidivist offenders, correctional officers, and police officers, and supported by literature study. The collected data were analyzed using a descriptive qualitative method to obtain a comprehensive understanding of the research problems. The results show that the factors causing theft by recidivists consist of internal and external factors. Internal factors include psychological conditions such as mental pressure, frustration, low self-control, and established criminal habits. Meanwhile, external factors include unfavorable social environments, peer influence, economic pressure, and lack of family support. In addition, the effectiveness of the law and sanctions is considered not yet optimal, due to weaknesses in inmate rehabilitation, limited coordination among law enforcement institutions, and social stigma against former prisoners that hinders social reintegration. The conclusion of this study is that theft committed by recidivists in Kupang City is influenced by a combination of internal and external factors, as well as the ineffectiveness of law enforcement and sanctions in preventing repeated crimes. Therefore, more comprehensive efforts are needed, including improving the quality of rehabilitation in correctional institutions, strengthening inter-agency coordination, and increasing social support from the community to prevent recidivism